What Happened to Village lnfrastructure and Public Services During the Economic Crisis in Indonesia? - Darja, Jesse; Suryadarma, Daniel; Suryahadi, Asep; Sumarto, Sudarno (Institute for Economic and Social Research, 2005)
.